CURRENT TRENDS AND PROBLEMS OF DEVELOPMENT OF THE HOTEL MARKET OF KRASNOYARSK KRAI - Tatyana Nikolaevna Safronova (Science and Innovation Center Publishing House, 2019)
Development of the hotel markets of regions is connected with diversification of a tourist product, search of the new directions. One of major factors of development of regional tourism is change of economic, social, demographic conditions of development of regions. In work socio-economic indexes of Krasnoyarsk krai are presented, statistics of the market of hotel services and tourism for 2014–2018, their structure are analysed. Problems and current trends of development of the tourist and hotel markets of Krasnoyarsk krai are defined.